1989
DOI: 10.1177/030098588902600508
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammatory Cells with Epithelial Cell Characteristics in Teleost Fishes

Abstract: Certain cells that participate in the chronic inflammatory response of teleost fishes have many features typical of epithelioid cells of mammals. Such features include high metabolic activity, frequent phagolysosomes, and cytoplasmic interdigitations between adjacent cells; however, the epithelioid granulomas formed in response to certain diseases in teleost fishes also have several features associated with epithelial cells. Cases of ulcerative mycosis or acid-fast bacterial infection in Atlantic menhaden (Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 11 publications
6
46
0
1
Order By: Relevance
“…Desmosomes are generally considered to be characteristic of true epithelial or mesothelial cells (Ghadially 1988), although desmosome-like structures have been observed between histiocytes in certain human dermatopathies, as well as rat carageenan granuloma (Caputo & Gianotti 1979, Monis & Valentich 1986. Noga et al (1989) also observed the presence of desmosomes in piscine granulomatous inflammation, and postulated that either (1) the capacity of macrophages to elaborate desmosomes is a primitive characteristic that has been lost in avian and mammalian orders, or (2) the cells involved in certain types of piscine inflammation derive from a nonmacrophage lineage (i.e. mesothelial cells).…”
Section: Discussionmentioning
confidence: 99%
“…Desmosomes are generally considered to be characteristic of true epithelial or mesothelial cells (Ghadially 1988), although desmosome-like structures have been observed between histiocytes in certain human dermatopathies, as well as rat carageenan granuloma (Caputo & Gianotti 1979, Monis & Valentich 1986. Noga et al (1989) also observed the presence of desmosomes in piscine granulomatous inflammation, and postulated that either (1) the capacity of macrophages to elaborate desmosomes is a primitive characteristic that has been lost in avian and mammalian orders, or (2) the cells involved in certain types of piscine inflammation derive from a nonmacrophage lineage (i.e. mesothelial cells).…”
Section: Discussionmentioning
confidence: 99%
“…Observations of this disease among moray eels in the wild (Ray Davis, personal communication) indicate that this disease is neither an artifact of captivity nor just a husbandry problem for aquaria, and the importance of this disease to wild populations of moray eels merits further investigation. Granulomatous inflammatory lesions in fish have been reported to occur in association with infection by higher bacteria, fungi, and algae, and as reactions to foreign bodies (11,18,23). In one aquarium facility, similar granulomatous skin lesions among captive green moray eels were attributed to fiberglass components of the exhibit's artificial reef structure (9).…”
Section: Discussionmentioning
confidence: 99%
“…They have also been encountered in the liver, pancreas and peritoneal serosa of minnows Phoxinus phoxinus (L.), infected with the larvae of the nematode Raphidascaris acus Bloch, 1779 (Dezfuli et al 2000). With reference to the presence of epithelioid cells in the capsule, Noga et al (1989) suggested that piscine epithelioid cells may represent an alternative type of epithelial inflammatory cell. These cells were also noted in the infected tissues of P. phoxinus (Dezfuli et al 2000).…”
Section: Resultsmentioning
confidence: 99%